The provision of central venous access, transfer of critically ill patients and advanced airway management.: Are advanced critical care practitioners safe and effective?. (August 2019) - Denton, Gavin; Green, Lindsay; Palmer, Marion; Jones, Anita; Quinton, Sarah; Giles, Simon; Simmons, Andrew; Choyce, Andrew; Munnelly, Sean; Higgins, Daniel; Perkins, Gavin D; Arora, Nitin
Advanced critical care practitioners are a new and growing component of the critical care multidisciplinary team in the United Kingdom. This audit considers the safety profile of advanced critical care practitioners in the provision of central venous catheterisation and transfer of ventilated critical care patients without direct supervision and supervised drug assisted intubation of critically ill patients. The audit showed that advanced critical care practitioners can perform central venous cannulation, transfer of critically ill ventilated patients and intubation with parity to published UK literature.